Urbanization and child nutritional outcomes - Amare, Mulubrhan; Arndt, Channing; Abay, Kibrom A.; Benson, Todd (International Food Policy Research Institute, 2017)
In this paper, we investigate the implications of urbanization on child nutritional outcomes using satellite-based nighttime light intensity data as a proxy for urbanization and urban growth. We employ two rounds (2008 and 2013) of geo-referenced and nationally representative Demographic and Health Survey (DHS) data from Nigeria. The DHS data provide detailed anthropometric measures of child nutritional outcomes along with a series of control variables. We merge these geo-referenced DHS data with nighttime light intensity data for the survey clusters in which the DHS sample households reside. This nighttime light introduces a continuous gradient of urbanization permitting investigation of the implications of urbanization on child nutritional outcomes along an urbanization continuum. The longitudinal nature of the nighttime data allows us to examine the dynamics of urbanization and its implication on child nutrition.